Glucose metabolism determines resistance of cancer cells to bioenergetic crisis after cytochrome-c release - Huber, Heinrich J (Nature Publishing Group, 2011)
Many anticancer drugs activate caspases via the mitochondrial apoptosis pathway. Activation of this pathway triggers a concomitant bioenergetic crisis caused by the release of cytochrome-c (cyt-c). Cancer cells are able to evade these processes by altering metabolic and caspase activation pathways. In this study, we provide the first integrated system study of mitochondrial bioenergetics and apoptosis signalling and examine the role of mitochondrial cyt-c release in these events. In accordance with single-cell experiments, our model showed that loss of cyt-c decreased mitochondrial respiration by 95% and depolarised mitochondrial membrane potential ΔΨ(m) from −142 to −88 mV, with active caspase-3 potentiating this decrease. ATP synthase was reversed under such conditions, consuming ATP and stabilising ΔΨ(m). However, the direction and level of ATP synthase activity showed significant heterogeneity in individual cancer cells, which the model explained by variations in (i) accessible cyt-c after release and (ii) the cell's glycolytic capacity. Our results provide a quantitative and mechanistic explanation for the protective role of enhanced glucose utilisation for cancer cells to avert the otherwise lethal bioenergetic crisis associated with apoptosis initiation.